Indigenous Climate Change Adaptation Planning Using a Values-Focused Approach: A Case Study with the Gitga'at Nation. Issue Volume 34:Issues 3(2014) (October 2014) - Reid, Michael G.; Hamilton, Colleen; Reid, Sarah K.; Trousdale, William; Hill, Cam; Turner, Nancy; Picard, Chris R.; Lamontagne, Cassandra; Matthews, H. Damon
Local values and knowledge can be important components in creating robust climate change adaptation strategies for marginalized communities. Incorporating local values into the climate change planning process in a structured way and effectively using local knowledge not only improves the identification of priority actions for climate change adaptation, but also supports successful implementation. Much of climate change adaptation planning in recent years identifies actions derived from expert-driven vulnerability assessments and adaptation actions. Yet the values of each community influence how climate change impacts are perceived, and what adaptation actions are locally acceptable and will have local buy-in for implementation. Thus, it is important that planning incorporates local values if the goal is successful adaptation to climate change. This paper provides one approach for addressing this through a participatory, values-based process for climate change adaptation planning. The approach is contextualized through a case study of the Gitga'at Nation, located in northern coastal British Columbia, Canada, where key values were found to be culturally important food sources, culture, environmental resources, self-sufficiency, health, infrastructure to enable us to live well, and Gitga'at pride and cooperation. These values were used throughout the planning process to contextualize climate change impacts on Gitga'at members' way of life and to develop and evaluate adaptation actions. It is hoped that this case study provides further proof of the utility of values-based planning in the context of adaptation planning for marginalized communities.